STUDENTS’ PERCEPTION ON THE USE OF DUOLINGO APPLICATION IN LEARNING ENGLISH DURING COVID-19 - Khairul Fadilah (UIN Sumatera Utara, 2022)
This research aims to find out how students' perception of the use of Duolingo application in learning English. This research was conducted in SMP Swasta IT Al-Fattah Desa Lama. A qualitative method was used for this research and there were 20 students in the ninth class as the sample of this research. In collecting the data, this research used a questionnaire and interview. The findings took the result that most students agree and gave a positive response than the negative one of the use of Duolingo application in learning English during Covid-19. Duolingo application gave the benefits and contribution to both the students and teachers in learning English. 1) This application made the students feel enjoyable in learning English and made the learning process became fun during this Covid 19 pandemic; 2) This application gave a significant impact and increased students' knowledge and improved their English during this Covid 19 pandemic; 3) Using this application, the students had a chance to improve their English whenever they want to learn it. The conclusion could be taken that the students had positive responses and perceptions in using Duolingo application for learning English.